O ensino na atenção primária à saúde em escolas médicas do estado de São Paulo - Bravo, Victoria Angela Adami [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The educational programofmedical universities have been changingto conform to the National CurricularGuidelines for medical undergraduates (DCNmed), implemented in 2001 through resolution nº4 of the National Education Council.All medical schools in Brazil must adapt their curricula to the National CurricularGuidelines, which includes the primary health care education. Under this perspective, the educational projects of the surveyed schools were evaluatedwithin these principles and the insertion of the student in the primary health care, in order to understand how schools are introducing students to primary health care, what space it occupies in the program and what importance it has in the formation of physicians today. This is a qualitative study. When organizing the samples, we used the following criteria to select schools: one federal, one state public school and one private school. Selected schools should have had their educational programs and projects on their institutional website. We chose three medical schools from São Paulo state following the criteria above mentioned. The study consisted of a desk review of educational projects, collected on the school websites, therefore public domain information, with a predetermined script intended to identify the conceptions and primary health care intervention practices in the reviewed documents. Additionally, we conducted semi-structured interviewswith the medicine course coordinators and coordinators responsible for disciplines in which the students access primary health care, so that we can understand how professionals perceive and prepare the implementation of primary health care, within the formative context of these courses.This study also points the curricularpedagogic proposals (PPCs) with structural and educational problemsrooted in the understanding of theproposal. Theseproblems even affected the role of primary health caregiving an idea that the primary health care, despite ...

Curriculares Nacionais (DCN) dos cursos de graduação em medicina que foram instituídas em 2001, pela resolução n°4 do Conselho Nacional de Educação. Todas as escolas médicas do Brasil devem adequar seus currículos as Diretrizes Curriculares Nacionais, o que inclui, entre outras reformulações, a inclusão do ensino na atenção primária à saúde (APS). Sob essa ótica o trabalho tem por objetivo analisar como é entendida a proposta formativa dos cursos de medicina frente a interação entre universidade serviço e comunidade nos Projetos Pedagógicos, nas falas dos coordenadores dos cursos de medicina e na fala dos coordenadores das disciplinas em que têm como cenário de prática a atenção primária. Trata-se de uma pesquisa exploratória, com metodologia qualitativa. Na organização da amostra, utilizaram-se os seguintes critérios de seleção das escolas: uma escola federal, uma estadual e uma privada. As escolas selecionadas deveriam ter os currículos e Projetos pedagógicos disponíveis no sítio da rede virtual da instituição. Objetivando-se cumprir os critérios elencados acima foram selecionadas três escolas médicas do estado de São Paulo. O estudo foi realizado por meio de análise documental dos projetos pedagógicos, coletados no sítio da rede virtual das escolas, logo de domínio público, com roteiro pré estabelecido que buscou identificar as concepções e formas de intervenção da atenção primária apresentada nos referidos documentos. Na sequencia, foram realizadas entrevistas semiestruturadas com os coordenadores dos cursos de medicina e coordenadores responsáveis por disciplinas em que os alunos tem como campo de prática a APS no intuito de compreender como esses profissionais entendem, elaboram e implementam o contexto formativo desses cursos da APS. Foi utilizada a análise de conteúdo para interpretação dos dados obtidos. A partir da leitura do material documental e das entrevistas e ...
Keywords: Cuidados primários de saúde; Ensino superior; Escolas para profissionais de saúde; Planejamento educacional; Primary health care; Health occupations schools